Analisis Implementasi Kebijakan Pengelolaan Sampah Rumah Tangga di Kabupaten Muara Enim Berdasarkan Teori Edwards III - Namira, Fania; Azhar, Azhar (Universitas Medan Area, 2025)
This study analyzes the implementation of household waste management policies in Muara Enim Regency based on the implementation theory of George C. Edwards III, which includes four main variables: communication, resources, disposition, and bureaucratic structure. The background of this research is the increasing volume of household waste that has not been balanced with an effective and sustainable management system. This research employs a qualitative descriptive method, utilizing regional policy documents, field observations, and interviews with relevant parties. The results of the study show that the implementation of waste management policies has not been optimal. Inhibiting factors include a lack of policy socialization, limited transportation facilities and infrastructure, weak coordination between agencies, and low public awareness of independent waste management. Improvement efforts should focus on enhancing cross-sector communication, strengthening the capacity of human resources and facilities, and empowering the community to maintain environmental cleanliness. This research emphasizes the importance of collaboration between the government and the community to realize effective, efficient, and sustainable waste management in Muara Enim Regency.